Facile Synthesis of Holothurian‐Like γ‐MnS/Carbon Nanotube Nanocomposites for Flexible All‐Solid‐State Supercapacitors. Issue 8 (26th June 2017) - Hou, Xiaoyi; Peng, Tao; Yu, Qiuhong; Luo, Rongjie; Liu, Xianming; Zhang, Yingge; Wang, Yange; Guo, Yan; Kim, Jang‐Kyo; Luo, Yongsong
Abstract: The holothurian‐like γ‐MnS/carbon nanotube (CNT) nanocomposites are successfully fabricated through a facile two‐step hydrothermal method. The γ‐MnS@CNT hybrid nanocomposite is an attractive electrode material for supercapacitors as it exhibits excellent electrochemical performance with a high specific capacitance of 641.9 F g −1 and cyclic stability of 94.6 % retention after 3000 cycles at a current density of 0.5 A g −1, which are superior to those of CNTs and pure γ‐MnS nanoparticles. Furthermore, the as‐fabricated all‐solid‐state supercapacitor reveals remarkable specific capacitance of 263.5 F g −1, high capacitance retention, and a high energy density of 36.6 Wh kg −1 at a power density of 0.5 kW kg −1 . The device maintains its supercapacitor performance well, even under bending or twisting states, indicating the excellent mechanical stability and flexibility of the device. The impressive results demonstrate the great opportunity for practical application of this metal sulfide‐based composite in high‐performance, flexible energy storage devices and wearable electronics. Abstract : Flexible energy storage : γ‐MnS nanoparticles coated on carbon nanotube (CNT) backbones form a holothurian‐like γ‐MnS@CNT nanocomposite. The corresponding γ‐MnS@CNT electrodes delivered excellent electrochemical performance with a high specific capacitance of 641.9 F g −1 and inspiring cycling stability. The device maintains its supercapacitor performance well, even under bending or twisting, indicating possible applications in flexible/wearable, lightweight, and self‐powered energy storage devices.